APENDIKS A SCHOLAR, A TEACHER AND A TRUE GUIDE (a Tribute to Asghar Ali Engineer) - Qutub Jahan (Media Syari'ah, 2017)
During my university days I have done a fair reading of Dr. Asghar Ali Engineer’s work on Shah Bano issue. I profoundly recall during a presentation of my seminar paper on ‘Shah Bano case and rights of Muslim woman’, thanks to my reader of sociology who suggested some good books to refer to prepare my paper, and it was highly appreciated by the panel. I still remember our Sociology department in my University, (SNDT Women’s University), was holding a workshop and had invited Anna Hazare and they wanted to invite someone championing for woman’s right as well and I requested them to invite Dr. Asghar Ali Engineer. My professors too were great admirer of Dr. Engineer’s articles but unfortunately we could not get his dates.